2022
DOI: 10.1371/journal.pclm.0000028
|View full text |Cite
|
Sign up to set email alerts
|

How can carbon labels and climate-friendly default options on restaurant menus contribute to the reduction of greenhouse gas emissions associated with dining?

Abstract: In this study, we aimed to understand how restaurants can contribute to climate change mitigation via menu design. We investigated two types of interventions: changing the configuration of menu entries with variable side dishes so that the most climate-friendly option is set as the default and indicating the greenhouse gas emission of each dish via carbon labels. In an online simulation experiment, 265 participants were shown the menus of nine different restaurants and had to choose exactly one dish per menu. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…or "less methane")-a potential opportunity to differentiate products in the market, especially as emissions claims roll out on menus around the world (Betz et al, 2022;Kruse et al, 2021). When these elements were found, they were typically within the body of long "flavor-text" (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…or "less methane")-a potential opportunity to differentiate products in the market, especially as emissions claims roll out on menus around the world (Betz et al, 2022;Kruse et al, 2021). When these elements were found, they were typically within the body of long "flavor-text" (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…If designed to be simple and clear, information on GHG emissions or certain other environmental issues had an impact on choices in experimental studies and reduced the consumption of environmentally harmful products [68,69]. A similar effect was shown on menus [70]. However, the indication of GHG emissions has a greater effect on consumers who are already environmentally conscious and who already consume comparatively little meat [71].…”
Section: Support At the Moment Of Decision And Activating Influencing...mentioning
confidence: 93%
“…However, research in this area is still developing (Reisch & Sunstein, 2021), and the effectiveness of nudges seems to vary between nudge types and context. For example, research examining plant-based diets has suggested that carbon labels do not work effectively in real-world settings (Kaljonen et al, 2020), even though they do in online experiments (Betz et al, 2022), and that the impact of positive food descriptions are mixed, with Saulais et al (2019) finding that 'dish of the day' descriptions increased plant-based food consumption among European consumers while Zhou et al (2019) did not. Furthermore, some nudges can have unintended adverse effects by reducing or reversing the desired behaviour (Mertens et al, 2022), known as 'boomerang effects' (Osman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%